How’s Life After the Collapse? Populism as a Representation Linkage and the Emergence of a Populist/Anti-Populist Political Divide in Italy (1994–2018) - Zanotti, Lisa (Frontiers in Political Science, 2021)
Populism is a hot topic in academia. The causes of this phenomenon have received much attention with many studies focusing on the role of the high level of unresponsiveness of mainstream parties in triggering a populist response. In this respect, in many cases, populist parties have become a relevant electoral force in the concomitance with an electoral decline of mainstream political options, mostly in the last decades (Hernández and Kriesi 2016; Hobolt and Tilley 2016; Kriesi and Pappas 2015). This article considers the situation in which the whole party system's unresponsiveness reaches its zenith, and the party system collapses. A collapse is the result of the incapacity of most of the parties in the system to fulfill their basic function, i.e., represent the interests of voters. In this situation, none of the types of linkages—programmatic, clientelist, or personalist—that tie parties and voters function properly. Empirical observation shows that in those cases populism can serve as a sort of linkage to re-connect parti(es) and voters on the basis of the moral distinction between ‘the people’ and ‘the elite’. Through a discursive strategy of blame attribution, populists can attract a large portion of the vote. At this point, its opposing ideology—anti-populism—also arouses. In other words, populism/anti-populism may result in a political cleavage that structures the party system by itself or, more frequently, with other cleavages. To elucidate this argument, the paper explores the case of Italy between 1994 and 2018. The electoral relevance of populist parties translated first into a discursive cleavage, which, in turn, changed the space of competition with the emergence of a new political axis, namely populism/anti-populism (see Stavrakakis and Katsambekis 2018; Stavrakakis 2014; Pappas 2014; Ostiguy 2009). This paper's central claim is that the dynamics of partisan competition cannot be understood by overlooking the populism/anti-populism political divide. The conclusion examines one implication of the emergence of this political cleavage, namely the incentives for coalition building. In fact, when populism with anti-populism structure, at least partially, the party system, this may affect the determinants of parties' coalition-building choices since it changes the space of interparty competition.